Emotional Intelligence and Suicidal Ideation in Indonesian Adolescents: Dynamics, Contributing Factors, and Pathways to Resilience - Hardini Sabatiana Dewi; Arthur Huwae (Journal of Psychological Perspective, 2025)
Suicide ideation among adolescents has emerged as a pressing global health crisis, with recent national surveys in Indonesia reporting that over 1% of youth experience such thoughts and many face related mental health challenges. This study explores the dynamics and influencing factors of emotional intelligence (EI) in adolescents who experience suicide ideation. Employing a qualitative case study design, five participants aged 15–22 years with a history of suicide ideation were purposively selected. Data were gathered through in-depth, semi-structured interviews guided by Goleman’s EI framework and analyzed using Miles and Huberman’s interactive model. Results reveal that all participants exhibited underdeveloped EI, characterized by difficulties in recognizing and regulating emotions, limited self-control during emotional crises, and impaired relationship skills. Key factors shaping these EI patterns included negative parenting, traumatic experiences, and insufficient social support. Despite these challenges, some adolescents demonstrated adaptive coping through creative expression and supportive relationships. The findings highlight the importance of family and community support as protective factors and underscore the need for targeted interventions to enhance EI and resilience in vulnerable youth. This study contributes critical insights for mental health practitioners and educators aiming to prevent adolescent suicide.